Histo-pathological pattern of endometrial biopsy in females with abnormal uterine bleeding: a retrospective study in tertiary care hospital of Haryana - Lata, Gagan; Sharma, Susmita; Kaur, Sukhbir Pal; Gulia, Sandhya Panjeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: This study aimed to know the various histo-pathological patterns of endometrial biopsy and their incidence in patients of AUB. Methods: Patients in the age group between 21-75 years who had presented with AUB and underwent endometrial biopsy from 1st January 2017 to 31st December 2019 were included. The endometrial biopsy specimens which were already taken from patients with AUB were scrutinized for histopathological pattern. Various patterns of histo-pathology of endometrial biopsy were noted and studied. Results: Most common age group which was affected was between 36-40 years. The endometrial biopsies and curetting’s on histopathology revealed various patterns ranging from normal endometrium to malignancy. Patterns of normal cyclical endometrium (proliferative and secretory phases) were the most common patterns. Conclusions: Evaluation of women with AUB is important around the perimenopausal age group to detect any atypical and malignant changes and intervene early. Histopathological examination in correlation to radiological findings remain the standard procedures for diagnosis.